2016
DOI: 10.1016/j.ecohyd.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Model analysis of check dam impacts on long-term sediment and water budgets in Southeast Arizona, USA

Abstract: The objective of this study was to evaluate the effect of check dam infrastructure on soil and water conservation at the catchment scale using the Soil and Water Assessment Tool (SWAT). This paired watershed study includes a watershed treated with over 2000 check dams and a Control watershed which has none, in the West Turkey Creek watershed, Southeast Arizona, USA. SWAT was calibrated for streamflow using discharge documented during the summer of 2013 at the Control site. Model results depict the necessity to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 53 publications
2
33
0
Order By: Relevance
“…Water-harvesting techniques using rock detention structures were originally developed by native tribes (Fish and Fish 1984). Norman et al (2014Norman et al ( , 2015Norman et al ( , 2016 have documented increased surface water and vegetation health at riparian sites treated with these erosion control structures (ECSs) in southeastern Arizona, USA, and northern Sonora, Mexico. However, the impacts of watershed restoration techniques on downstream surface water and on groundwater aquifers are undocumented.…”
Section: Introductionmentioning
confidence: 99%
“…Water-harvesting techniques using rock detention structures were originally developed by native tribes (Fish and Fish 1984). Norman et al (2014Norman et al ( , 2015Norman et al ( , 2016 have documented increased surface water and vegetation health at riparian sites treated with these erosion control structures (ECSs) in southeastern Arizona, USA, and northern Sonora, Mexico. However, the impacts of watershed restoration techniques on downstream surface water and on groundwater aquifers are undocumented.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, SWAT ITs were used to model a constructed wetland placement effect on water quality (Wang et al 2008); wetlands' influence on flood mitigation, peak-flow reduction through wetland water retention, and increased evapotranspiration (Demissie and Khan 1993;Hattermann et al 2006;Babbar-Sebens et al 2013); and to simulate nutrient retention in natural and constructed wetlands (White and Bayley 2001;Vache et al 2002;Cooper 2009). SWAT ITs were also used to estimate sediment and nutrient retention in reservoirs (Mishra et al 2007;Bosch 2008;Liu et al 2014); to assess dam and check dam impact on local water, sediment, and nutrient yields (Mishra et al 2007;Ouyang et al 2011;Zhang et al 2011;Liu et al 2014;Norman and Niraula 2016); to model reservoir placement feasibility (Zhang et al 2012); to calculate reservoir water availability for municipal purposes (Brauer et al 2015); and to model and account for reservoir influence in SWAT modeling (Kirsch et al 2002;Bosch 2008;Wang and Xia 2010;Liu et al 2016;Vigiak et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Porto et al () used the radionuclides of 137 Cs and 210 Pb ex as sediment tracers to investigate the sediment budget in a small forested catchment of southern Italy, the results confirmed that 137 Cs and 210 Pb ex measurements can provide a valuable tool for quantifying both erosion and sediment redistribution compared with the traditional monitoring techniques. The Soil and Water Assessment Tool model was also used to evaluate the effect of check dam on soil and water conservation at the catchment scale, modelling results indicated that approximately 630 Mg of sediment was estimated to be stored behind check dams over the 3–year simulation at the West Turkey Creek watershed in southeast USA (Norman & Niraula, ). Meanwhile, researches attempted to use the deposition record of check dam or reservoir and the monitoring data at the watershed outlet to validate sediment yield model, such as WATEM/SEDEM model (Alatorre et al , ) and Annualized Agricultural Non‐point Source model (Zema et al , ; Zema et al , ).…”
Section: Introductionmentioning
confidence: 99%